Kualitas Telur Puyuh Selama Penyimpanan dan Temperatur yang Berbeda - Arizona, Rizki; Ollong, Abdul Rahman (Fakultas Peternakan Universitas Papua, 2020)
The objective of this study is to determine the quality of quail eggs stored at room temperature and refrigerated. The variables evaluated are weight loss, shape index, air cell size, and the height of both the albumen and the yolk. Several factors, such as storage time and temperature could affect the quality of quail eggs. Therefore, we investigated the impact of both factors. The samples used for this experiment include 360 quail eggs. This research uses a completely randomized factorial design with two treatments. The treatments consisted of storage time (0, 7, 14, and 21 days) and temperature (room temperature and refrigerator). Each treatment was replicated 9 times. Analyses of variance had been applied to analyze the data and followed with Duncan’s test to see whether there was a significant difference between treatments. The result showed that storage time and temperature have significant effects on weight loss of the eggs, air cell size, and albumen and yolk height. The interaction between treatments had a significant impact on air cell size and yolk height. Refrigerated storage for 21 days showed the best result.